System Development on the Uncertainty Propagation Analysis on Estimation of Environmental Radiation Exposure - Mike Susmikanti; Entin Hartini; Nursinta Adi Wahanani; Khairina Ns (Indonesian Journal of Physics, 2010)
This paper describes the system development to measure the uncertainty propagation analysis on estimation of environmental radiation exposure. The estimation of environmental radiation exposure is one of the important things that needs to be calculated as a result of nuclear activities in nuclear facilities from exploration and mining, nuclear fuel processing, nuclear power station, nuclear fuel repository or radioactive waste management. The nuclides that result from the radioactive waste are very hazardous to environment. One of the most hazardous materials resulted from the radioactive waste is Radon (222Rn). People who are exposed to excessive Radon emission might have lung cancer. However, the estimation of the Radon exposes to the environment is quite complicated as there are many parameters to be considered. Moreover, the estimation also includes several assumptions about the process of the exposure. Therefore, the main topic of this paper is the uncertainty of the input parameters of the model to be developed. Furthermore, this paper will apply the Monte Carlo method to estimate the propagation analysis of Radon exposure in nuclear waste facility. In addition, the developed system will make use of Nuclear Regulatory Committee (NRC) Regulatory Guide model to estimate the propagation analysis from radioactive storage and waste management. Finally, the system software will be developed using open source and multiplatform environments.